2013
DOI: 10.1037/a0029949
|View full text |Cite
|
Sign up to set email alerts
|

Predicting purchase decision: The role of hemispheric asymmetry over the frontal cortex.

Abstract: This article examines how approach motivation as indexed by electroencephalographic (EEG) asymmetry over the prefrontal cortex predicts purchase decision when brand and price are varied. In a within-subjects design, the participants were presented purchase decision trials with 14 different grocery products (seven private label and seven national brand products) whose prices were increased and decreased while their EEG activity was recorded. The results showed that relatively greater left frontal activation (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
85
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 66 publications
14
85
0
1
Order By: Relevance
“…Although FA was significantly reduced in both left and right IFG (clusters 10 and 18) in alcoholics compared to control participants (see Table 2), it was the left IFG (cluster 18) that was more strongly associated with indices of drinking severity. This is interesting because structures of the dorsolateral prefrontal cortex, and in particular the IFG, have been implicated in processes related to self-control, decision-making, and reward sensitivity (Davidson & Irwin, 1999; Ravaja, et al, 2013). Specifically, there is the suggestion that approach-based decisions and withdrawal-based decisions may be lateralized to the left and right IFG, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although FA was significantly reduced in both left and right IFG (clusters 10 and 18) in alcoholics compared to control participants (see Table 2), it was the left IFG (cluster 18) that was more strongly associated with indices of drinking severity. This is interesting because structures of the dorsolateral prefrontal cortex, and in particular the IFG, have been implicated in processes related to self-control, decision-making, and reward sensitivity (Davidson & Irwin, 1999; Ravaja, et al, 2013). Specifically, there is the suggestion that approach-based decisions and withdrawal-based decisions may be lateralized to the left and right IFG, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the available findings, we expected to find widespread abnormalities in FA in WM tissue among currently abstinent alcoholic individuals, particularly in the corpus collosum and in WM tracts underlying the frontal cortex. We were particularly interested in WM microstructure in the dorsolateral prefrontal cortex and the inferior frontal gyrus (IFG), because these areas have been implicated in processes related to self-control, decision-making, response inhibition, and reward sensitivity (Davidson & Irwin, 1999; Ravaja, et al, 2013). The importance of response inhibition and lateralization of reward-based decision making has been directly implicated in addictive behavior (see Goldstein & Volkow, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ravaja et al . () go further. Their results ‘showed that relatively greater left frontal activation (i.e., higher approach motivation) during the predecision period predicted an affirmative purchase decision’ (Ravaja et al .…”
Section: Neuroscientific Studies Of Decision‐making Within a Marketinmentioning
confidence: 99%
“…Frontal asymmetry scores (L – R alpha) for the proximal and distal recordings were baseline adjusted for each participant so that they reflected changes in asymmetry, following past research on state frontal alpha asymmetry (e.g., Allen et al, 2001; Ravaja et al, 2013). The resultant asymmetry scores for the proximal and distal recordings were highly correlated, r = 0.63, p < 0.001.…”
Section: Resultsmentioning
confidence: 99%